Systematic literature review on the application of Problem-Based Learning model in chemistry education - Gazali, Fauzana; Rahayu, Sri; Munzil, Munzil; Wonorahardjo, Surjani; Alam, Muhammad Dimar (Eclética Química, 2025)
Problem-based learning (PBL) has seen significant growth in recent years, but its effective implementation remains a challenge. Therefore, this study undertakes a systematic literature review to synthesise the research patterns, challenges, and approaches employed in chemistry education. PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) methodology was employed in analysing publications within journals indexed in Scopus and Web of Science. A total of 523 papers have been found using some keywords. Following a thorough assessment, 35 publications were selected for in-depth analysis. The study found that PBL implementation varies depending on four primary variables: thinking skills, problem-solving abilities, conceptual comprehension, and argumentation skills. PBL concerns include issues like malnutrition, obesity, waste management, climate change, pollution, and green chemistry. Common instructional steps of PBL include problem orientation, student organisation, independent study, group investigation, reporting, and evaluation. Several challenges were found in applying PBL, including time limitation, instructor proficiency, student characteristics, and technical implementation of PBL. These findings are expected to complement the references for future research on PBL.